LINGUISTIC STUDY OF THE CONCEPT OF "NATURE" THROUGH RUSSIAN PHRASEOLOGISMS - Nanshanlo A. (Vestnik Issyk-Kulʹskogo universiteta, 2025)
The article presents a linguistic study of the concept of "nature" based on Russian idioms. Idioms reflecting natural phenomena, animals, and vegetation are an important part of the linguistic worldview and contain the rich cultural and mental experience of the people. The paper analyzes examples of stable expressions related to nature, such as "a bear's service" (an unhelpful favor), "like a fish in water" (feeling comfortable), and "dragging the cat by the tail" (procrastinating), which illustrate the metaphorical perception of natural objects and phenomena in relation to human behavior and situations. Special attention is given to idioms associated with weather and climatic conditions, such as "like snow on your head" (something unexpected) and "raining cats and dogs" (heavy rain), which convey the perception of suddenness, intensity, or everyday natural realities. The study concludes that nature in Russian idioms serves not only as a reflection of the surrounding world but also as a means of describing national character, experiences, and emotions. Thus, the concept of "nature" through idioms helps to better understand the linguistic and cultural features of the Russian people and their relationship with nature.